2011
DOI: 10.1002/bit.23288
|View full text |Cite
|
Sign up to set email alerts
|

Culture temperature modulates aggregation of recombinant antibody in cho cells

Abstract: During production of therapeutic monoclonal antibodies (mAb), it is highly desirable to remove and control antibody aggregates in the manufacturing process to minimize the potential risk of immunogenicity to patients. During process development for the production of a recombinant IgG in a CHO cell line, we observed atypical high variability from 1 to 20% mAb aggregates formed during cell culture that negatively impacted antibody purification. Analytical characterization revealed the IgG aggregates were mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…It has a direct influence on cell growth, nutrient consumption and productivity (Fan et al 2010;Marchant et al 2008). Moreover, temperature is to be associated with product quality, including glycosylation patterns (Ahn et al 2008), aggregation (Gomez et al 2012) and cysteine variants (Gomez et al 2010). However, the effect of culture temperature on mAb charge variation and the mechanism of how hypothermic condition affects charge variation are rarely known.…”
Section: Introductionmentioning
confidence: 98%
“…It has a direct influence on cell growth, nutrient consumption and productivity (Fan et al 2010;Marchant et al 2008). Moreover, temperature is to be associated with product quality, including glycosylation patterns (Ahn et al 2008), aggregation (Gomez et al 2012) and cysteine variants (Gomez et al 2010). However, the effect of culture temperature on mAb charge variation and the mechanism of how hypothermic condition affects charge variation are rarely known.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of LC and HC mRNA abundance, the assembly and folding of antibody can be limited by the low expression of the ER proteins. It has been shown that low expression of ER proteins in a small ER volume can result in antibody aggregation [34].…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments supported these results by demonstrating that low H chain polypeptide synthesis limits Ab production. Several other publications have studied some effects of H and L chain imbalance on Ab folding and protein production (Gomez et al 2012;Li et al 2005; Schlatter et al 2005; Sung et al 2004). Li et al (2005) have demonstrated using bi-cistronic constructs of the encephalo myocarditis virus internal ribosome entry site, a significant increase in Ab production in HEK293T cells when the expression of H chains exceeded that of L ones.…”
Section: Discussionmentioning
confidence: 99%